Probiotics, prebiotics, and synbiotics for patients with autism spectrum disorder: a meta-analysis and umbrella review - Rahim, Fakher; Toguzbaeva, Karlygash; Qasim, Nameer Hashim; Dzhusupov, Kenesh O.; Zhumagaliuly, Abzal; Khozhamkul, Rabiga (Frontiers in Nutrition, 2023)
Background and objective The potential impact of gut health on general physical and mental well-being, particularly in relation to brain function, has led to a growing interest in the potential health advantages of prebiotics, probiotics, and synbiotics for the management of ASD. A comprehensive meta-analysis and systematic review was conducted in order to evaluate the effectiveness and protection of many drugs targeted at manipulating the microbiota in the treatment of ASD. Methods The present study employed a comprehensive examination of various electronic databases yielded a total of 3,393 records that were deemed possibly pertinent to the study. RCTs encompassed a total of 720 individuals between the ages of 2 and 17, as well as 112 adults and participants ranging from 5 to 55 years old, all of whom had received a diagnosis of ASD. Results Overall, 10 studies reported Autism-Related Behavioral Symptoms (ARBS). Regarding the enhancement of autism-related behavioral symptoms, there wasn’t a statistically significant difference between the intervention groups (combined standardized mean difference = −0.07, 95% confidence interval: −0.39 to 0.24, Z = 0.46, p = 0.65). We observed that in the patients with ASD treated with probiotic frontopolar’s power decreased significantly from baseline to endpoints in beta band (Baseline: 13.09 ± 3.46, vs. endpoint: 10.75 ± 2.42, p = 0.043, respectively) and gamma band (Baseline: 5.80 ± 2.42, vs. endpoint: 4.63 ± 1.39, p = 0.033, respectively). Among all tested biochemical measures, a significant negative correlation was found between frontopolar coherence in the gamma band and TNF-α (r = −0.30, p = 0.04). Conclusion The existing body of research provides a comprehensive analysis of the developing evidence that indicates the potential of probiotics, prebiotics, and synbiotics as therapeutic therapies for ASD. Our findings revealed that those there was no significant effect of such therapy on autism-related behavioral symptoms, it has significant effect on the brain connectivity through frontopolar power in beta and gamma bands mediated by chemicals and cytokines, such as TNF-α. The psychobiotics showed no serious side-effects.